The Production and Consumption Accounting Principles as a Guideline for Designing Environmental Tax Policy - Mònica Serrano (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper evaluates two alternative tax policies aimed at reducing atmospheric pollutant emissions. One based upon an environmental tax that burdens directly firms emissions, and the other one that burdens both directly and indirectly household consumptions emissions. Applying input-output approach, we reallocate the emissions generated in the economy according to the responsibility definition, i.e. the production or the consumption accounting principle. Afterwards, we analyse the effects on the products prices of implementing an ad-quantum environmental tax based on the Producer Pays Principle (PPP) and/or on the User Pays Principle (UPP). The results obtained, show that both PPP and UPP environmental tax have the same effect on the final products prices. However, the price of the intermediate products is only affected by the PPP environmental tax, whereas the UPP environmental tax keeps the prices unchanged.
Keywords: C67; H23; Q53; 330; Input-Output Analysis; Environmental Taxes; Atmospheric Pollutants; Ökosteuer; Input-Output; Luftreinhaltung; Theorie